Viral Infections of the Central Nervous System in Africa - Kakooza-Mwesige, Angelina; Tshala-Katumbay, Desire; Julianoe, Sharon L. (Brain research bulletin, 2019)
Viral infections are a major cause of human central nervous system infection, and may be associated with significant mortality, and long-term sequelae. In Africa, the lack of effective therapies, limited diagnostic and human resource facilities are especially in dire need. Most viruses that affect the central nervous system are opportunistic or accidental pathogens. Some of these viruses were initially considered harmless, however they have now evolved to penetrate the nervous system efficiently and exploit neuronal cell biology thus resulting in severe illness. A number of potentially lethal neurotropic viruses have been discovered in Africa and over the course of time shown their ability to spread wider afield involving other continents leaving a devastating impact in their trail. In this review we discuss key viruses involved in central nervous system disease and of major public health concern with respect to Africa. These arise from the families of Flaviviridae, Filoviridae, Retroviridae, Bunyaviridae, Rhabdoviridae and Herpesviridae. In terms of the number of cases affected by these viruses, HIV (Retroviridae) tops the list for morbidity, mortality and long term disability, while the Rift Valley Fever virus (Bunyaviridae) is at the bottom of the list. The most deadly are the Ebola and Marburg viruses (Filoviridae). This review describes their epidemiology and key neurological manifestations as regards the central nervous system such as meningoencephalitis and Guillain-Barré syndrome. The potential pathogenic mechanisms adopted by these viruses are debated and research perspectives suggested.
Keywords: CNS viral infections; Ebola; Herpes; HIV; Rabies; Zika